2015
DOI: 10.1016/j.molcel.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

BET Bromodomain Inhibition Suppresses the Function of Hematopoietic Transcription Factors in Acute Myeloid Leukemia

Abstract: Summary The bromodomain and extraterminal (BET) protein BRD4 is a validated drug target in leukemia, yet its regulatory function in this disease is not well understood. Here, we show that BRD4 chromatin occupancy in acute myeloid leukemia closely correlates with the hematopoietic transcription factors (TFs) PU.1, FLI1, ERG, C/EBPα, C/EBPβ, and MYB at nucleosome-depleted enhancer and promoter regions. We provide evidence that these TFs, in conjunction with the lysine acetyltransferase activity of p300/CBP, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
332
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(355 citation statements)
references
References 54 publications
22
332
0
1
Order By: Relevance
“…Cell type-specific distribution of BRD4 is accomplished by TF recruitment to their enhancers (41). Our study showed that PAX3-FOXO1 can direct de novo recruitment of BRD4 to specific chromatin sites when introduced into human fibroblasts, accompanied by opening of chromatin and acetylation of H3K27 at enhancers proximal to key RMS genes.…”
Section: Discussionmentioning
confidence: 69%
“…Cell type-specific distribution of BRD4 is accomplished by TF recruitment to their enhancers (41). Our study showed that PAX3-FOXO1 can direct de novo recruitment of BRD4 to specific chromatin sites when introduced into human fibroblasts, accompanied by opening of chromatin and acetylation of H3K27 at enhancers proximal to key RMS genes.…”
Section: Discussionmentioning
confidence: 69%
“…We also found that p300 helps to recruit BRD4 to the BATF promoter region. In fact, recent studies have demonstrated that BRD4 and p300 form a complex to transcriptionally activate several other genes such as MYC and FOS (50,51). Our studies of pharmacological modulation of BET and p300 point to an acetylation-dependent signaling mechanism, since JQ1 directly inhibits BET protein binding to acetylated lysine residues in chromatin and C646 inhibits the catalytic acetyltransferase activity of p300.…”
Section: Discussionmentioning
confidence: 73%
“…The latter are known to mediate long-range dysregulation of key oncogenes in hematologic cancers 52 and to coordinate activity of key hematopoietic transcription factors in leukemia. 66 Alternatively, disruption of BRD4 interaction with transcription and elongation factors (eg, polymerase II, positive transcription elongation factor b, Mediator, and Activator) may be part of the mechanism by which JQ1 inhibits lincRNA-3q expression. Finally, intrinsic histone acetylase activity of BRD4 itself may play a role.…”
Section: Discussionmentioning
confidence: 99%